The structural and electrical properties of (1-x)BaTiO3 - XBaFe0.5Nb0.5O3 ceramics - Uraiwan Intatha (2018)
The structural and electrical properties of (1-x) BaTiO3- xBaFe0.5Nb0.5O3ceramics system were investigated as a function of the BaFe0.5Nb0.5O3content by X-ray diffraction (XRD), dielectric and ferroelectric measurement techniques. Studies were performed on the samples prepared by solid state reaction for x = 0, 0.2, 0.4 and 0.6. The XRD analysis demonstrated that with increasing BFN content in (1-x)BT-xBFN, the structural change occurred from the tetragonal to the cubic phase at room temperature. Changes in the dielectric, ferroelectric and piezoelectric behavior were then related to these structures depending on the BFN content. Copyright © Taylor &Francis Group, LLC.